Growth Performance and Carcass Characteristics of Lambs Fed Concentrate Mixtures Containing Varying Levels of Palm Oil Decanter Cake - Devika, Dharmana; Kishore, Konka Raja; Kumar, Dhulipalla Srinivas; Seshaiah, Chappidi Venkata (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
A study was conducted to evaluate the effect of feeding concentrate mixture containing varying levels of palm oil decanter cake (PODC) on growth performance and carcass characteristics in Nellore brown ram lambs. In a completely randomized design, 18 lambs were divided into three equal groups of six each and allotted to three dietary treatments (T1 T2 and T3) comprising of green fodder Super Napier and concentrate mixture (20% CP) containing PODC at 0, 10, and 20%, respectively. The body weight gain (kg) and average daily gain (g/d) of lambs improved significantly (p <0.05) at 20% level of PODC in concentrate mixture with non-significant differences in feed efficiency (kg feed/kg gain). Results revealed a significant decrease in feed cost/kg gain by Rs. 7.81 and 29.06 in T2 and T3 compared to T1 control group. Carcass studies, however, revealed no effect on various carcass characteristics. It was concluded that PODC could be incorporated up to 20% in the diets of growing lambs for improved growth performance without altering carcass characteristics.